2000
DOI: 10.1002/(sici)1096-8628(200021)97:1<72::aid-ajmg10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement dysfunction in schizophrenia: A heritable characteristic for enhancing phenotype definition

Abstract: The occurrence of ocular motor dysfunction in schizophrenia patients and their first-degree biological relatives is remarkably consistent, suggesting that abnormal smooth pursuit and saccadic oculomotion are heritable characteristics that can be used to identify gene carriers for schizophrenia. Saccadic system dysfunction probably reflects a generalized deficit in prefrontal cortical functioning, rather than a specific deficit in saccade system functioning. Although abnormal smooth pursuit has also been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…Hence, temporal information helps patients to overcome inappropriate semantic clustering. This is in line with the desinhibition deficit in schizophrenia and the assumption that task-irrelevant information impedes patients' performances, see, e.g., [84]. Patients have difficulties suppressing an imminent stimulus-driven response (according to semantic content) in favor of a voluntary action (by integrating temporal information).…”
Section: Discussionsupporting
confidence: 77%
“…Hence, temporal information helps patients to overcome inappropriate semantic clustering. This is in line with the desinhibition deficit in schizophrenia and the assumption that task-irrelevant information impedes patients' performances, see, e.g., [84]. Patients have difficulties suppressing an imminent stimulus-driven response (according to semantic content) in favor of a voluntary action (by integrating temporal information).…”
Section: Discussionsupporting
confidence: 77%
“…For example, it has been suggested that smooth pursuit is an endophenotype for schizophrenia (Calkins & Iacono, 2000; Allen, Griss, Folley, Hawkins, & Pearlson, 2009). Investigating the neurological and genetic basis of individual differences in a candidate endophenotype may provide insights into the biological basis of a clinical condition more easily than attempting to correlate the condition itself with biological variation.…”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…Basal ganglia dysfunction, assessed with functional MRI, has been reported in schizophrenia and their unaffected siblings (13-15). Also, the caudate is involved in smooth pursuit and saccadic eye movement (16,17), which have been shown to be abnormal in individuals with schizophrenia and their relatives (18,19).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Basal ganglia dysfunction, assessed with functional MRI, has been reported in schizophrenia and their unaffected siblings (13-15). Also, the caudate is involved in smooth pursuit and saccadic eye movement (16,17), which have been shown to be abnormal in individuals with schizophrenia and their relatives (18,19).Enlargement of basal ganglia volume in schizophrenia has been reported (20-22); however, these findings have been generally attributed to treatment with older generation ("typical") antipsychotic medications that act primarily as antagonists at D2-type dopamine receptors in the basal ganglia (23,24). Volumetric abnormalities in various brain areas have been reported in the non-psychotic first-degree relatives of schizophrenia patients (25-27), but there have been relatively few studies of basal ganglia structure in this population.…”
mentioning
confidence: 99%